ANALISIS PDRB, INFLASI, UPAH MINIMUM PROVINSI, DAN ANGKA MELEK HURUF TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA TENGAH TAHUN 1990-2011 - Hajji, Muhammad Shun; SBM, Nugroho (Diponegoro Journal of Economics, 2013)
This study aim to analyze Â factors which having an effect to open-unemployment level in Central Java Province at 1990 to 2011. Ordinary least squares (OLS) will be used as regression model with the dependent variable, open-unemployment level and four independent variables, that are domestic regional gross product, inflation, province minimum wage, and the number of alphabetist. The result show that province minimum wage and the number of alphabetist influential manifestly and significantly to the open-unemployment level. In future, province minimum wage policy need a depth monitoring, so as to persistent over the market equilibrium and the labor welfare guaranteed. The value of province minimum wage which came near 100% indicate the high education quality of society in that region. This case need a special attention from government to create job demand in formal sector to anticipate the castaway potential resource which is the one of development support. Key Words: Open-Unemployment Level, Domestic Regional Gross Product, Inflation, Province Minimum Wage, Number of Alphabetist, Time Series